Cucumber and honey soaking reduces hypertension in the elderly - Soesanto, Edy; Zulino, Salsabella (South East Asia Nursing Research, 2021)
Hypertension is a condition of increasing a person's blood pressure beyond normal limits, causing increased morbidity and mortality. Hypertension can be reduced by consuming cucumber which contains potassium which inhibits the release of renin so that there is an increase in sodium and water excretion. In addition, it can also be reduced by consuming honey which can prevent the formation of plaque attached to the walls of blood vessels so that it can eliminate bad cholesterol for the body. This study aimed to determine the effect of giving cucumber and honey water immersion on Elderly Hypertension. This study used a Quasy Experimental design with a Pretest and Posttest with Control Group design. Sampling using a simple random sampling technique. The sample in this study amounted to 30 elderly people using the paired sample t-test statistical test. The results showed that the average blood pressure of the intervention group before being given the cucumber and honey water immersion was 153.6/84 mmHg and after it was 148.3/82.1 mmHg. The average blood pressure of the control group before being given the cucumber and honey water immersion was 158.5/80.2 mmHg and after it was 163.5/80.2 mmHg with p = 0.000. In the results of the independent sample test the intervention group before being given therapy, namely Sig. (2-tailed) = 0.027, the control group before treatment was Sig. (2-tailed) = 0.045. While the test results of the intervention group after being given therapy are Sig. (2-tailed) = 0.124, the control group after being given therapy is Sig. (2-tailed) = 0.139. There is an effect of giving cucumber and honey water immersion therapy on changes in blood pressure in the elderly with hypertension. But there is no difference in the average blood pressure of the Hypertensive Elderly. It is expected that the elderly with hypertension can make cucumber and honey water immersion as an alternative therapy to reduce hypertension